COMPARATIVE EFFECT OF TEN ORGANIC FERTILIZER SOURCES ON GROWTH AND YIELD OF LONG CAYENNE PEPPER IN TWO AGRO-ECOLOGICAL ZONES OF NIGERIA - Akinfasoye, Akindele Joel; Fagbayide, Julius A; Ajayi, Oluwakayode Emmanuel; Ogunniyan, Dotun J (Journal of Agricultural Sciences (Belgrade), 2018)
The objective of this study was to screen 10 organic fertilizer sources for nutrient contents and their effects on growth and yield of long cayenne pepper. Organic fertilizers including Tithonia compost (TC),Poultry manure from battery cage (PMB), Poultry manure dip-litter(PMD), Pacesetter organic fertilizer (POF), Sunshine organic fertilizer (SOF), Ayeye organic fertilizer (AOF), Brewery waste (BW), Cow dung (CD), Oil palm bunch ash (OPBA), Cocoa pod husk (CPH)were collected at some specific locations in Oyo, Osun and Ondo States. The experiment was a 2 × 11 factorial experiment fitted into a randomized complete block design consisting of 10 organic fertilizer sources and controlat two locations (Ibadan and Ogbomoso) in 2008. 130 kg N ha-1of each of organic fertilizer was applied one week before transplanting.Six weeks old pepper seedlings were transplanted into a plot of 3m × 2m (6m2) at one per hill. Growth and yield data collected were subjected to analysis of variance (ANOVA) andleast significant difference (LSD) at P <0.05 was used to compare the means. Result of the experiment reveled that overall macronutrient content of the ten evaluated organic fertilizer sources was of the order SOF > OPBA = CPH > AOF > TC > POF > PM = CD > BW > PMD. All the organic fertilizers were significantly enhanced better growth and yield of pepper than the control. The best three organic fertilizer sources at both locations in terms of fruit length were TC = SOF = PM. Fruit size at Ogbomoso was relatively bigger than that of Ibadan. The total fruit yield was highest under TC, SOF, PM and PMD at both locations. In conclusion, variations existed in nutrient composition of the organic fertilizer. Meanwhile,TC, PM, PMD and SOF were significantly similar in their ability to improve pepper yield. Moreover PM, TC and SOF significantly enhance the vegetative growth of pepper.